Screening for depression in cancer patients receiving radiotherapy: Feasibility and identification of effective tools in the NRG Oncology RTOG 0841 trial. Issue 3 (10th November 2016) - Wagner, Lynne I.; Pugh, Stephanie L.; Small, William; Kirshner, Jeffrey; Sidhu, Kulbir; Bury, Martin J.; DeNittis, Albert S.; Alpert, Tracy E.; Tran, Binh; Bloom, Beatrice F.; Mai, Julie; Yeh, Alexander; et al.
Abstract : BACKGROUND: Brief tools are needed to screen oncology outpatients for depressive symptoms. METHODS: Patients starting radiotherapy for the first diagnosis of any tumor completed distress screening tools, including the 9‐item Patient Health Questionnaire (PHQ‐9), the 2‐item Patient Health Questionnaire (PHQ‐2), the National Comprehensive Cancer Network Distress Thermometer (NCCN‐DT), and the Hopkins Symptom Checklist (HSCL) (25‐item version). Patients exceeding validated cutoff scores and a systematic sample of patients whose screening was negative completed the Structured Clinical Interview for DSM‐IV (SCID) mood disorder modules via telephone. RESULTS: Four hundred sixty‐three patients from 35 community‐based radiation oncology sites and 2 academic radiation oncology sites were recruited. Sixty‐six percent of the 455 eligible patients (n = 299) were women, and the eligible patients had breast (45%), gastrointestinal (11%), lung (10%), gynecologic (6%), or other cancers (27%). Seventy‐five (16.5%) exceeded screening cutoffs for depressive symptoms. Forty‐two of these patients completed the SCID. Another 37 patients whose screening was negative completed the SCID. Among the 79 patients completing the SCID, 8 (10.1%) met the criteria for major depression, 2 (2.5%) met the criteria for dysthymia, and 6 (7.6%) met the criteria for an adjustment disorder. The PHQ‐2 demonstrated good psychometric properties for screening for mood disorders with a cutoff score of ≥3 (receiver operating characteristic area under the curve [AUC], 0.83) and was comparable to the PHQ‐9 ( > 9; AUC = 0.85). The NCCN‐DT did not detect depression (AUC = 0.59). CONCLUSIONS: The PHQ‐2 demonstrated good psychometric properties for screening for mood disorders, which were equivalent to the PHQ‐9 and superior to the NCCN‐DT. These findings support using the PHQ‐2 to identify patients in need of further assessment for depression, which has a low prevalence but is a clinically significant comorbidity. These findings could inform the implementation of distress screening accreditation standards. Cancer 2017;123:485–493. © 2016 American Cancer Society . Abstract : Addressing psychosocial needs has been increasingly recognized as an integral component of quality cancer care, and the association between depression and cancer outcomes underscores the importance of identifying effective strategies for the detection of mood disorders among survivors. The 2‐item Patient Health Questionnaire demonstrates good psychometric properties for screening patients for mood disorders, which are equivalent to the longer 9‐item Patient Health Questionnaire and superior to the National Comprehensive Cancer Network Distress Thermometer. See also pages 382–6.